Radiometric dating of Middle Pleistocene carbonates: assessing consistency and performance of the U–Th and U–Pb dating methods - T. J. Pollard; J. D. Woodhead; R. N. Drysdale; R. L. Edwards; X. Li; A. N. Wainwright; M. Pythoud; H. Cheng; H. Cheng; J. C. Hellstrom; I. Isola; E. Regattieri; et al. (Geochronology)
The U–Th and U–Pb dating methods are widely employed for radiometric dating of Pleistocene carbonates, such as speleothems and corals. The U–Th dating method has been progressively refined over recent decades, largely through advances in mass spectrometry, and is now capable of providing accurate and precise ages for carbonates as old as ∼ 650 000 years under optimal circumstances. Similarly, the U–Pb method, traditionally restricted to dating pre-Quaternary materials, has been adapted in recent years for dating young carbonates. As a result, there is now substantial overlap in the applicable age range of these two dating methods but, thus far, only limited assessment of their consistency and relative performance when dating samples over this shared age interval.